2001
DOI: 10.1161/01.hyp.38.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Region Around the Sa Gene on Rat Chromosome 1

Abstract: Abstract-A region with a major effect on blood pressure (BP) is located on rat chromosome 1 in the vicinity of the Sa gene, a candidate gene for BP regulation. Previously, we observed a single linkage peak for BP in this region in second filial generation rats derived from a cross of the spontaneously hypertensive rat (SHR) with the Wistar-Kyoto rat (WKY), and we have reported the isolation of the region containing the BP effect in reciprocal congenic strains (WKY.SHR-Sa) and (SHR.WKY-Sa) derived from these an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 32 publications
5
47
0
Order By: Relevance
“…Analysis of SHR and WKY SNP alleles at the blood pressure QTL in the Sisa1a congenic strain suggests that the interval flanked by Bmal1 and Spon1 may correspond to an ancestral haplotype containing hypertensive gene(s) originally present in outbred Wistar rats and selected in SHR. The observation of an apparent complete genetic conservation between SHR and WKY for 170 consecutive markers Ͼ16.6 Mb of this QTL in the congenic strain WISA1 (10.7 cM, 29.2 Mb) distal to the Sisa1a region (33) supports the applicability of this strategy to select positional candidate genes (data not shown).…”
Section: Discussionsupporting
confidence: 53%
“…Analysis of SHR and WKY SNP alleles at the blood pressure QTL in the Sisa1a congenic strain suggests that the interval flanked by Bmal1 and Spon1 may correspond to an ancestral haplotype containing hypertensive gene(s) originally present in outbred Wistar rats and selected in SHR. The observation of an apparent complete genetic conservation between SHR and WKY for 170 consecutive markers Ͼ16.6 Mb of this QTL in the congenic strain WISA1 (10.7 cM, 29.2 Mb) distal to the Sisa1a region (33) supports the applicability of this strategy to select positional candidate genes (data not shown).…”
Section: Discussionsupporting
confidence: 53%
“…Single QTLs identified in genome scans typically fractionated into multiple, closely linked QTLs, often with opposite effects. In mouse genetics this finding emerged from studies that chased single effects through the creation of congenics and includes QTLs influencing seizures (Legare et al 2000), obesity (Stylianou et al 2004), growth , blood pressure (Frantz et al 2001;Alemayehu et al 2002;Garrett and Rapp 2002a,b;Ariyarajah et al 2004), diabetes (Podolin et al 1998), antibody production (Puel et al 1998), and infection (Bihl et al 1999). In flies, highresolution mapping efforts using a higher density of recombination or performing quantitative complementation tests to deficiencies revealed similar complexity for QTLs affecting wing shape (Weber et al 1999(Weber et al , 2001Mezey et al 2005), longevity De Luca et al 2003;Wilson et al 2006), resistance to starvation stress (Harbison et al 2004), mating behavior (Moehring and Mackay 2004), olfactory behavior (Fanara et al 2002), locomotor reactivity (a startle response) , and numbers of sensory bristles (Dilda and Mackay 2002).…”
Section: Genetic Architecture: Many Loci Of Small Effectmentioning
confidence: 99%
“…Another possibility is suggested by our recent findings from genetic dissection of the RNO1 BP QTL region. 8 Nonoverlapping subcongenic strains spanning the region introgressed in WKY.SHR-Sa were found to carry BP effects, indicating that there are at least 2 QTLs that influence BP in this region. 8 Therefore, it is possible that the difference seen between the transplant groups represent the phenotypic expression of only one of these QTLs.…”
Section: Clemitson Et Al Tissue Specificity Of Chromosome 1 Bp Qtl 295mentioning
confidence: 99%
“…7 The minimal introgressed segment in WKY.SHR-Sa is Ϸ31 cM long between D1Rat 199 and D1Rat 117, and the maximal interval is Ϸ54 cM between D1Wox 29 and D1Wox 10. 7,8 The objective of the present study was to see whether young bilaterally nephrectomized WKY that receive a kidney transplant from WKY.SHR-Sa rats developed a significantly higher BP than that of WKY receiving a kidney transplant from another WKY. The study design is shown in Figure 1.…”
Section: Strains and Study Designmentioning
confidence: 99%
See 1 more Smart Citation